Factors influencing the utilization of antenatal and postnatal care services by women of reproductive age group: a cross-sectional study in rural community of Maharashtra - Bhansali, Pratiksha Santosh; Avachat, Shubhada Sunil; Deshmukh, Gaurav Vijayrao (International Journal Of Community Medicine And Public Health, 2022)
Background: Antenatal care (ANC) and postnatal care (PNC) care services intended to secure and improve maternal health are utilized only to a limited extent. Therefore, this study was conducted to assess various barriers and association of various sociodemographic factors like age, education, economic status and religion with the utilization of services. This revealed the reasons which avert the ladies from utilising the services adequately. Methods: 150 women residents of Uruli Kanchan, a village in Pune district of Maharashtra, having at least 1 child below the age of five years were selected by simple random sampling technique. The data was collected by house-to-house survey and interview technique. Results: In the present study, better utilization of ANC services was observed (99.234%) as compared to PNC services (65.33%). Education, good socioeconomic conditions and religion were the factors which greatly influenced the utilization of PNC services. Lack of desire and awareness of PNC visits (in 55% women) was an important factor for underutilization of PNC services. Lack of trust towards government services (by 34.02%) women was observed.70% of women showed satisfaction towards the maternal and child health care (MCH) services provided by the government. Conclusions: Women showed high level of utilization of ANC services as compared to PNC services which still need a lot of attention and awareness. Women show lack of trust in the government facility.